2013
DOI: 10.1002/bse.1836
|View full text |Cite
|
Sign up to set email alerts
|

Changing Behaviour: Successful Environmental Programmes in the Workplace

Abstract: There is an increasing focus on improving the pro-environmental attitudes, behaviour and habits of individuals, whether at home, in education, travelling, shopping or in the workplace. This article focuses on the workplace by conducting a multi-disciplinary literature review of research that has examined the influence of organization-based behaviour change initiatives. The review includes only research evidence that measured actual environmental performance (e.g. energy use) rather than solely using self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(177 citation statements)
references
References 51 publications
6
167
1
3
Order By: Relevance
“…[45] This is encouraging, as in our data and earlier study, [10] staff's attitudes were considered to be a substantial barrier to progress in environmental responsibility. On the other hand, another study [47] found that a pro-environmental attitude was not necessarily required, as favorable work structures, systems, cultures and rewards, and staff's awareness of practical sustainable actions, may already be enough to change their behavior. This supports our findings about the need for diverse organizational support in environmental work.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] This is encouraging, as in our data and earlier study, [10] staff's attitudes were considered to be a substantial barrier to progress in environmental responsibility. On the other hand, another study [47] found that a pro-environmental attitude was not necessarily required, as favorable work structures, systems, cultures and rewards, and staff's awareness of practical sustainable actions, may already be enough to change their behavior. This supports our findings about the need for diverse organizational support in environmental work.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
“…In addition to receiving education, people also need to be motivated to behave in an environmentally friendly way [14] by other approaches. [16] Administrators could, for example, give work communities feedback on their performance [29] and reward their success financially [43,47] and publicly. Also, a sense of community motivates people to act pro-environmentally, [48] particularly if it benefits their private life.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
“…Researchers now broadly recognize the contextual (rather than purely environmental) factors influencing the human-building interaction [10][11][12][13][14][15][16][17]. Explorations regarding the achievement of energy-efficient usage in the building sector are today established around the understanding of the socio-technical link between building occupants' behavior and the use of building technologies, energy services, and controls [9].…”
Section: Needs For Interdisciplinary Studiesmentioning
confidence: 99%
“…These variables typically include indoor and outdoor environmental (e.g., indoor/outdoor air temperature, illuminance level, CO2 concentration), contextual (e.g., time of the day, day of the week), and personal traits (gender, age, and user profiles). Recently, models accounting for influential contextual factors such as ease of control, freedom of movement, knowledge of technology, and usability factors are discussed within the building engineering community [10,11,15,16,23] …”
Section: Motivational Driversmentioning
confidence: 99%
See 1 more Smart Citation